Per operative findings in repeat cesarean section - Sinha, Parul; Gupta, Uma; Singh, Jyotsna; Srivastava, Anand; Chauhan, Shilpi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: Cesarean section is the commonest obstetric procedure done worldwide. Incidence of cesarean section is increasing giving it a term “repeat cesarean section”. Repeat cesarean section makes future obstetrics performances and abdominal exploration risky. After any Laparotomy it is fairly common to develop scar tissue, or adhesion. The scarring and adhesion formation is known to increase the major complications rate from 4.3% to 12.5% depending on the number of previous section. Intra peritoneal adhesions have an incidence of 5.5% to 42.5%. Methods: An observational prospective study was conducted in Obstetrics and gynecology department of Era’s Lucknow Medical College, Lucknow. Total 80 cases of repeat cesarean sections were included. The case histories and intra operative findings were recorded. Results: Intra peritoneal adhesions of varied types were seen in majority of cases, out of which the most commonly seen adhesion was between parietal peritoneum and anterior surface of uterus 24(30%) and adhesion between bladder and uterus 24(30%). Conclusions: Chances of developing adhesions increases with each cesarean section, which leads to increase in morbidity of women. Thus cases of previous cesarean section should be educated about routine antenatal care.